Actividades lúdicas para el desarrollo de las capacidades físicas en estudiantes de 10mo año, Unidad Educativa “Diez de Agosto” - Falcón Moreta, Emma Lisbeth (2025)
The present research work refers to recreational activities for the development of physical abilities of tenth year students, since currently most young people have little knowledge about the importance of their execution, they do not express trust and security in the social, cultural and sporting spheres of their environment. The primary objective of the proposal is in a line of innovation because it aims to improve and enhance the development of the physical capabilities of the aforementioned students, with the design of a guide of recreational activities, which are according to the needs of each of them. thus developing interest, attitudes and motivation to participate. Within chapter 1 is the contextualization of the problematic situation, the statement of the problem, justification and objectives that guide the investigation. Chapter 2 presents the background and theoretical bases that underpin it, to have a better documented vision, Chapter 3 details the research design, the methodology used, then Chapter 4 presents the results in a systematized manner through statistical graphs, finally the conclusions and recommendations that we have reached after applying all the investigative work.